A Total Synthesis of Yellowish Aphid Pigment Furanaphin through Fries Rearrangement Assisted by Boron Trifluoride-Acetic Acid Complex - Nishimura, Taichi; Iwata, Takeki; Maegawa, Hironori; Nishii, Takeshi; Matsugasako, Masami; Kaku, Hiroto; Horikawa, Mitsuyo; Inai, Makoto; Tsunoda, Tetsuto (Synlett, 2012)
The yellowish aphid pigment furanaphin, isolated from Aphis spiraecola and possessing cytotoxicity against HL-60 (human promyelocytic leukemia-60) cells, was synthesized by utilizing the Fries rearrangement assisted with a BF3·2AcOH complex as a key step. It was confirmed that the complex effectively mediated the reaction even though the compounds had an electron-withdrawing substituent.
Keywords: dyes; pigments; Fries rearrangement; total synthesis; natural products